Nerve growth factor promotes differentiation and protects the oligodendrocyte precursor cells from in vitro hypoxia/ischemia - Baldassarro, Vito Antonio; Cescatti, Maura; Rocco, Maria Luisa; Aloe, Luigi; Lorenzini, Luca; Giardino, Luciana; Calzà, Laura (Frontiers in Neuroscience, 2023)
Nerve growth factor (NGF) is a pleiotropic molecule acting on different cell types in physiological and pathological conditions. However, the effect of NGF on the survival, differentiation and maturation of oligodendrocyte precursor cells (OPCs) and oligodendrocytes (OLs), the cells responsible for myelin formation, turnover, and repair in the central nervous system (CNS), is still poorly understood and heavily debated. Here we used mixed neural stem cell (NSC)-derived OPC/astrocyte cultures to clarify the role of NGF throughout the entire process of OL differentiation and investigate its putative role in OPC protection under pathological conditions. We first showed that the gene expression of all the neurotrophin receptors (TrkA, TrkB, TrkC, and p75NTR) dynamically changes during the differentiation. However only TrkA and p75NTR expression depends on T3-differentiation induction, as Ngf gene expression induction and protein secretion in the culture medium. Moreover, in the mixed culture, astrocytes are the main producer of NGF protein, and OPCs express both TrkA and p75NTR. NGF treatment increases the percentage of mature OLs, while NGF blocking by neutralizing antibody and TRKA antagonist impairs OPC differentiation. Moreover, both NGF exposure and astrocyte-conditioned medium protect OPCs exposed to oxygen-glucose deprivation (OGD) from cell death and NGF induces an increase of AKT/pAKT levels in OPCs nuclei by TRKA activation. This study demonstrated that NGF is implicated in OPC differentiation, maturation, and protection in the presence of metabolic challenges, also suggesting implications for the treatment of demyelinating lesions and diseases.